2013
DOI: 10.2337/dc13-0431
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Eating Behavior and Omission of Insulin in Adolescents Receiving Intensified Insulin Treatment

Abstract: OBJECTIVETo establish the prevalence of disturbed eating behavior (DEB) and insulin omission among adolescents with type 1 diabetes using intensive insulin treatment in a nationwide population-based study.RESEARCH DESIGN AND METHODSThe Diabetes Eating Problem Survey–Revised (DEPS-R) is a diabetes-specific screening tool for DEB. Clinical data and HbA1c were obtained from the Norwegian Childhood Diabetes Registry.RESULTSA total of 770 children and adolescents 11–19 years of age with type 1 diabetes completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
146
11
12

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(198 citation statements)
references
References 27 publications
29
146
11
12
Order By: Relevance
“…The burden of diabetes and of the associated therapy with a major focus on food and eating pattern may contribute to this type of disordered eating in T1DM males. Previous small studies indicated also a level of disturbed eating (e.g., insulin restriction or skipping, higher drive for thinness) in male T1DM patients (4,20,36). However, in small studies from Austria and Sweden, no male with T1DM had an ED based on DSM-IV criteria (4,20).…”
Section: Discussionmentioning
confidence: 97%
“…The burden of diabetes and of the associated therapy with a major focus on food and eating pattern may contribute to this type of disordered eating in T1DM males. Previous small studies indicated also a level of disturbed eating (e.g., insulin restriction or skipping, higher drive for thinness) in male T1DM patients (4,20,36). However, in small studies from Austria and Sweden, no male with T1DM had an ED based on DSM-IV criteria (4,20).…”
Section: Discussionmentioning
confidence: 97%
“…This accelerates microvascular complications. 93 NEUROLOGIC Brain atrophy changes occur as a result of the malnutrition of anorexia nervosa.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…It is crucial to assess for DEBs in this population, as they may further impair metabolic control and contribute to the development of complications such as diabetic retinopathy [28]. DEBs among those with T1D have been found to increase throughout adolescence, with approximately 33% of 14-16-year-old girls endorsing that they have engaged in these behaviors, while approximately 50% of 17 to 19 year olds reported engaging in DEBs [29,30]. DEBs may be less prevalent, yet still significant, among adolescent boys; approximately 7% of 14-16 year olds and 15% of 17-19 year olds with T1D reported engaging in DEBs [29,30].…”
Section: Ed Risk Factors Associated With Tidmentioning
confidence: 99%
“…Examination of this unique form of DEB, indicated that between 10.3-26.2% of girls and 1.4-4.5% of boys with diabetes have skipped doses of insulin to control weight, while 7.4-36.8% of girls and 1.4-9.4% of boys have administered lower doses of insulin than they were prescribed to control weight [29,30]. Jones and colleagues [27] found insulin omission to be the second most commonly utilized form of weight control among those with T1D, indicating that this behavior is common among those with T1D who are attempting to control weight.…”
Section: Ed Risk Factors Associated With Tidmentioning
confidence: 99%